Modelled salmon lice dispersion and infestation patterns in a sub-arctic fjord. (26th March 2018) - Skarðhamar, Jofrid; Albretsen, Jon; Sandvik, Anne D; Lien, Vidar S; Myksvoll, Mari S; Johnsen, Ingrid A; Asplin, Lars; Ådlandsvik, Bjørn; Halttunen, Elina; Bjørn, Pål Arne; ,
Abstract: Salmon lice infestation is a major challenge for the aquaculture industry in Norway, threatening wild salmonid populations and causing welfare problems for farmed salmon. Lice dispersion and infestation patterns are simulated by combining a high-resolution hydrodynamic model for the Norwegian coast and fjords with an individual-based model for salmon lice. We here present results from Altafjorden, a sub-arctic fjord with large stocks of wild salmonids, where the inner part is protected as a National Salmon Fjord. The outer part of the fjord hosts several fish farms, and our simulations demonstrate how ocean currents can disperse lice between farms as well as into the protected part of the fjord. The relative contributions from the farms in the different parts of the fjord depends on their locations relative to the currents and circulation patterns in the fjord. Knowledge of how the highly variable water currents disperse salmon lice within fjord systems is necessary for managing farm locations and production quotas, if the goal is to minimize infestation pressure on wild salmonids and between fish farms.